2023
DOI: 10.13057/biodiv/d240136
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay and molecular detection of insecticides resistance of Aedes aegypti, vector of dengue in Central Java Province, Indonesia

Abstract: Abstract. Sayono, Nurullita U, Handoyo W, Tyasningrum WS, Chakim I, Budiharjo A. 2023. Bioassay and molecular detectionsof insecticides resistance of Aedes aegypti, vector of dengue in Central Java Province, Indonesia. Biodiversitas 24: 300-307. The emergence of insecticide-resistant strains among Aedes aegyptipopulations hampered Dengue control programs in the endemic areas. Moreover, to understand the current situation and distribution of insecticide resistance status of Ae. aegypti to cypermethrin, malathio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Aedes albopictus displays phenotypic plasticity, enabling the development of strains adapted to a broad range of environmental conditions and optimal temperatures for survival and development (44; 45) . The mosquito has been collected along altitudinal transects, reaching up to 2100m above sea level in Nepal ( 46 ), and is commonly found above 1200 m in tropical environments (47; 48) . With a demonstrated capacity to outcompete Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Aedes albopictus displays phenotypic plasticity, enabling the development of strains adapted to a broad range of environmental conditions and optimal temperatures for survival and development (44; 45) . The mosquito has been collected along altitudinal transects, reaching up to 2100m above sea level in Nepal ( 46 ), and is commonly found above 1200 m in tropical environments (47; 48) . With a demonstrated capacity to outcompete Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Focus of research Cluster 1 (24 items) -Red Anopheles [27], c1534 [13], chemical [13], culex [17], culex quimquefasciatus [24], culicidae [105], cyfluthrin [10], cyhalothrin [29], deet [12], diptera [115], insecticide susceptibility status [11], kdr gene [11], knock [64], knockdown [123], malaria [25], malaria vector [20], mosquito coil [19], mosquito species [23], piperonyl butoxide [16], pirimiphos methyl [10], repellency [30], repellent [49], resistance ratio [24], transfluthrin [24].…”
Section: Cluster (Items) -Color Terms [Occurance]mentioning
confidence: 99%
“…Identification of kdr at allele f1534c in temephos-exposed Aedes aegypti and Aedes albopictus mosquitoes Cluster 3 (12 items) -Blue Aegypty mosquito [20], bali [21], dengue fever [26], denpasar [21], egg [19], human [15], indonesia [307], jakarta [18], resistance development [28], resistance phenotype [18], surveillance [22], v1016g mutation [14] Mutation analysis of the v1016g allele in dengue fever-causing mosquitoes in Denpasar, Bali and Jakarta Cluster 4 (12 items) -Yellow Aedes aegypti mosquito [31], central java [10], channel [130], cypermetrin [14], dengue vector aedes [12], haplotype [43], ile1016 [10], 1982w [13], s989p [46], vgsc [82], vgsc gene [21], voltage gated sodium channel [15] Identification of kdr in voltage gated sodium channel (VGSC) of Aedes aegypti mosquito Cluster 5 (11 items)purple Genotyping [34], insecticide use [13], resistance allele [12], s996 [10], southeast asia [15], target site resistance [10], v1023g [15], voltage sensitive sodium channel [17], vssc [24], vssc muattion [11], yogyakarta [2] Analysis of voltage sensitive sodium channel (VSSC) in mosquitoes in Yogyakarta Cluster 6 (9 items) -sky-blue Aedes aegypti [10], aegypti strain [12], chikv [11], dengue virus [23], denv [19], primary vector [18], virus …”
Section: Cluster (Items) -Color Terms [Occurance]mentioning
confidence: 99%
“…Continuous use of chemical insecticides can cause resistance to both mosquitoes and mosquito larvae (Valle et al 2019;Palomino et al 2022). As Sayono et al (2023) reported, the populations of Ae. aegypti resistant to cypermethrin 0.05% and temephos 0.02% are spread in several dengue endemic areas in Central Java, Indonesia.…”
Section: Introductionmentioning
confidence: 96%